Doping of nematic cyanobiphenyl liquid crystals with mesogen-hybridized magnetic nanoparticles - Appel, Ingo; Behrens, Silke (Physical chemistry, chemical physics, 2017)
Magnetic nanoparticles (MNPs) functionalized with (pro-)mesogenic ligands are implemented into a nematic liquid crystal (LC) and studied regarding both colloidal stability and magneto-optical behavior. In this study, the particle surface is specifically engineered to tune the MNP interactions with the LC host. For this purpose, four types of (pro-)mesogenic ligands (ML) are synthesized, which are composed of three structural parts, i.e., a rigid, LC motif (i.e., cyanobiphenyl) and a functional group for nanoparticle binding, both linked via a flexible spacer of different alkyl chain lengths. Electrostatically stabilized CoFe2O4 and γ-Fe2O3 nanoparticles with narrow size distribution and sizes below 3 nm are obtained via co-precipitation and subsequently functionalized to yield MNPML nanoparticles. Studies on the behaviour of the MNP@ML nanoparticles in the commercial LC host (i.e., 4-pentyl-4′-cyanobiphenyl (5CB)) in the bulk and in thin films in LC test cells, reveal the initial formation of some heterogeneities after transition from the isotropic to the nematic phase. Homogenous MNP@ML-5CB hybrids with long-term, colloidal stability, however, are obtained after magnetic separation of initially formed particle aggregates. In particular, MLs with carboxy groups and high structural flexibility (i.e., long linker lengths) are shown to be well suited to form stable MNP colloids, allowing for high MNP doping levels. As compared to undoped 5CB, the CoFe2O4@MLx-5CB hybrids show an increased sensitivity to the magnetic field, affecting the Fréedericksz transition. The strongest effect, however, is observed in magnetic and electric fields. The coupling of the ultrasmall, spherical MNPs with the LC director in the magnetic field suggests the formation of LC-induced, anisometric MNP clusters.